2013
DOI: 10.1016/j.visres.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to numerosity is not a unique visuospatial psychophysical predictor of mathematical ability

Abstract: HighlightsIndividual differences in numerosity acuity predict mathematical ability.We tested 300+ participants to see if this relationship is unique to numerosity.Visual numerosity and orientation task performance predicted mathematics scores.Performance improved with age, and males significantly outperformed females.This highlights links between mathematics and multiple visuospatial abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 61 publications
3
37
1
2
Order By: Relevance
“…In fact, w was not correlated with symbolic arithmetic performance. This finding is consistent with recent studies that report small or negligible correlation between performance in non-symbolic number comparison performance and math (Castronovo & Gobel, 2012; Fuhs & McNeil, 2013; Gobel et al, 2014; Holloway & Ansari, 2009; Inglis et al, 2011; Kolkman et al, 2013; Nosworthy et al, 2013; Price et al, 2012; Sasanguie et al, 2012; Sasanguie, Defever, et al, 2013; Sasanguie, Gobel, et al, 2013; Tibber et al, 2013; Wei et al, 2012). Moreover, many of the studies that show a reliable correlation between performance on a non-symbolic number comparison task and math did not adequately control for other non-numerical fluid processing performance measures (such as attention, memory, and executive function) that may be important for math ability (Anobile, Stievano, & Burr, 2013; Blair & Razza, 2007; Bull, Espy, & Wiebe, 2008; Clark, Pritchard, & Woodward, 2010; DeStefano & LeFevre, 2004; Geary, 2011; St Clair-Thompson & Gathercole, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, w was not correlated with symbolic arithmetic performance. This finding is consistent with recent studies that report small or negligible correlation between performance in non-symbolic number comparison performance and math (Castronovo & Gobel, 2012; Fuhs & McNeil, 2013; Gobel et al, 2014; Holloway & Ansari, 2009; Inglis et al, 2011; Kolkman et al, 2013; Nosworthy et al, 2013; Price et al, 2012; Sasanguie et al, 2012; Sasanguie, Defever, et al, 2013; Sasanguie, Gobel, et al, 2013; Tibber et al, 2013; Wei et al, 2012). Moreover, many of the studies that show a reliable correlation between performance on a non-symbolic number comparison task and math did not adequately control for other non-numerical fluid processing performance measures (such as attention, memory, and executive function) that may be important for math ability (Anobile, Stievano, & Burr, 2013; Blair & Razza, 2007; Bull, Espy, & Wiebe, 2008; Clark, Pritchard, & Woodward, 2010; DeStefano & LeFevre, 2004; Geary, 2011; St Clair-Thompson & Gathercole, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis has been supported by recent studies that show a correlation between individual precision of the ANS, as measured by w , and individual mathematical competence as measured by standardized math tests, often even after controlling for verbal ability and general intelligence measures (DeWind & Brannon, 2012; Gilmore, McCarthy, & Spelke, 2010; Halberda, Ly, Wilmer, Naiman, & Germine, 2012; Halberda, Mazzocco, & Feigenson, 2008; Libertus, Feigenson, & Halberda, 2011; Libertus, Odic, & Halberda, 2012; Mazzocco, Feigenson, & Halberda, 2011a, 2011b; Piazza et al, 2010). It should be noted, however, that many other studies now report negative findings (Castronovo & Gobel, 2012; Fuhs & McNeil, 2013; Gobel, Watson, Lervag, & Hulme, 2014; Holloway & Ansari, 2009; Inglis, Attridge, Batchelor, & Gilmore, 2011; Kolkman, Kroesbergen, & Leseman, 2013; Nosworthy, Bugden, Archibald, Evans, & Ansari, 2013; Price, Palmer, Battista, & Ansari, 2012; Sasanguie, De Smedt, Defever, & Reynvoet, 2012; Sasanguie, Defever, Maertens, & Reynvoet, 2013; Sasanguie, Gobel, Moll, Smets, & Reynvoet, 2013; Tibber et al, 2013; Wei, Yuan, Chen, & Zhou, 2012), creating a controversy over whether the ANS is causally related to symbolic math and if so exactly what mechanisms underlie this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…To provide an example, several studies have shown that precision of the visual sense of number predicts the level of mathematical achievements in school (Halberda et al, 2008). By contrast, a study by the author of this chapter suggests that this association is not unique-mathematical achievements are also associated with processing a variety of visual features (Tibber et al, 2013). Hypothetically, even showing that numerosity is a better predictor would not settle the argument, because "Leaky" accumulator comprising a circuit of two neurons with different activity timescales.…”
Section: Ams Accumulator or Ams Integrator?mentioning
confidence: 87%
“…These correlations, however, are relatively weak and only predict a small amount of variance in mathematical performance. Some researchers have also suggested that non-symbolic numerical abilities are part of a larger suite of visual-perceptual abilities that predict mathematics performance (Tibber et al, 2013). Others have argued that ANS acuity provides unique variance to predicting mathematical performance and that other similar perceptual tasks do not (Agrillo, Piffer, & Adriano, 2013), or that both ANS acuity and other perceptual tasks provide unique variance (Lourenco, Bonny, Fernandez, & Rao, 2012).…”
Section: Discussionmentioning
confidence: 99%